2007
DOI: 10.1530/eje-07-0388
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of high-sensitivity C-reactive protein and atherosclerosis in Japanese type 2 diabetic patients

Abstract: Background: The elevated level of high-sensitivity C-reactive protein (HSCRP) and aortic stiffness are associated with high mortality in type 2 diabetic patients. We tested the hypothesis that the HSCRP correlates with aortic stiffness and insulin resistance in type 2 diabetic patients. Material and methods: The study consisted of 46 Japanese patients with type 2 diabetes and high HSCRP group (0.3-1.0 mg/dl, age: 57G5 years, meanGS.D.) and a control group of 55 age-matched patients with low HSCRP group (!0.3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
2
2
1
Order By: Relevance
“…In contrast to previous studies we found no association of PWV with glycemic control in T2DM patients [9,21,43,44]. Furthermore, although inflammation, as assessed by hs-CRP, has been suggested to related to increased PWV in healthy subjects [45] as well as in hypertensive [46] and T2DM [47] patients, this has not been replicated in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies we found no association of PWV with glycemic control in T2DM patients [9,21,43,44]. Furthermore, although inflammation, as assessed by hs-CRP, has been suggested to related to increased PWV in healthy subjects [45] as well as in hypertensive [46] and T2DM [47] patients, this has not been replicated in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be emphasized that in all patients included in the study, the presence of any medical condition with features of inflammation was excluded, and ESR and leukocyte count were within normal limits. These results are consistent with data reported by other authors [5, 2226]. …”
Section: Discussionsupporting
confidence: 94%
“…5,6 Hs-CRP was not associated with PWV in Europeans with T2DM, 7,8 but associated with PWV in Asians with T2DM. 9,10 Yoon et al 3 reported positive association of sRAGE with PWV in T2DM, while we found negative association in normalbuminuric T2DM in this cohort. 11 Therefore, we aim to examine the association between hs-CRP and sRAGE with PWV and AI in a large multi-ethnic T2DM Asian cohort.…”
Section: Introductioncontrasting
confidence: 42%
“…7 In two studies reporting positive association, the median hs-CRP level of 4.5 mg/L or <1 mg/L is markedly different from our study. 9,10 The difference in hs-CRP levels ascribed to subject-selection (i.e. sampling-frame) and arterial stiffness measurement may all contribute to the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 99%